2020
DOI: 10.1101/2020.08.20.259747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and Cholinergic Anti-inflammatory Pathway:In silicoIdentification of an Interaction between α7 Nicotinic Acetylcholine Receptor and the Cryptic Epitopes of SARS-CoV and SARS-CoV-2 Spike Glycoproteins

Abstract: SARS-CoV-2 is the coronavirus that originated in Wuhan in December 2019 and has spread globally. The observation of a low prevalence of smokers among hospitalized COVID-19 patients has led to the development of a hypothesis that nicotine could have protective effects by enhancing the cholinergic anti-inflammatory pathway. Based on clinical data and on modelling and docking experiments we have previously presented the potential interaction between SARS-CoV-2 Spike glycoprotein and nicotinic acetylcholine recept… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…2 . As we have previously reported [[ 36 ] Preprint], α7 nAChRs appear to possess a LBD that could harbor toxin-like sequences identified in the Receptor Binding Domain (RBD) of the SARS-CoV and SARS-CoV-2 Spike glycoproteins (A7J8L4, P0DTC2). This specific LBD comprises residues preserved in the binding site of nAChRs and shows homology across the AChBP sequences that bind the agonists, as mentioned earlier.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 . As we have previously reported [[ 36 ] Preprint], α7 nAChRs appear to possess a LBD that could harbor toxin-like sequences identified in the Receptor Binding Domain (RBD) of the SARS-CoV and SARS-CoV-2 Spike glycoproteins (A7J8L4, P0DTC2). This specific LBD comprises residues preserved in the binding site of nAChRs and shows homology across the AChBP sequences that bind the agonists, as mentioned earlier.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described the molecular complexes of human α7 nAChR to both SARS-CoV and SARS-CoV-2 Spike glycoproteins, either in their open or closed conformation [[ 36 ], preprint]. We have observed that a significant portion of the "toxin-like" sequence in SARS-CoV and SARS-CoV-2 Spike can interact with the toxin binding sites of human α7 nAChR in the nM range, which is comparable with experimental supported Kds of well-known enzymatic interacting partners that produce stable protein complexes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted January 9, 2021. ; https://doi.org/10.1101/2021.01.07. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted January 9, 2021. ; https://doi.org/10.1101/2021.01.07.20248970 doi: medRxiv preprint acetylcholine receptor, which may compromise the cholinergic anti-inflammatory pathway 111 .…”
Section: Discussionmentioning
confidence: 99%